Volcanology progress and problems - edited by Christopher Jenkins
"This book discusses the problems related to the field of volcanology along with the progress witnessed in this field. The book presents individual research works on volcanological problems. The aim of this book is to serve as a valuable source of reference for graduate research students as well as researchers. It provides descriptive information regarding the wide field of volcanology dealing with several actively growing subject areas like volcanic terrain evolution or volcaniclastic-hosted mineral resource examination, volcano morphology, etc. It also presents insights into the areas like the sedimentary basin in China or the Russian Far East which are extremely remote and commonly less known to the global community. It illustrates the active evolution of volcanology during the past few decades."--Back cover.